Dampak Motivasi Kerja Terhadap Kinerja Karyawan PT. Cahaya Bintang Manise - Tuarita, Umiyati; Sahertian, Olivia Laura; Manuputty, Evandro Adolf Willem (Program Studi Administrasi Niaga STIA Said Perintah, 2022)
Managerial tool called human resource management. Employees are important assets of the company, the main driving force in carrying out company operations so that they should be developed, motivated to be more creative and independent in carrying out company activities. Work motivation is important for employees to improve and develop employee performance. The purpose of this study was to determine the effect of motivation on employee performance at PT Cahaya Bintang Manise, Salahutu District, Central Maluku Regency. This research is a quantitative research. Collecting data using questionnaires, interviews and observations. The population of this research is 30 employees of PT. Cahaya Bintang Manise and all of them are used as research samples. The data analysis technique used is simple linear regression with SPSS software. From the results of calculations using the SPSS 24 program, it can be seen that the coefficient of determination (R Square) obtained is 0.868. The influence of motivation on the performance of PT. Cahaya Bintang Manise employees is 86.8% while the remaining 13.2% is influenced by factors or variables. others that were not investigated in this study. The results of this study prove that motivation has an effect on employee performance. Employees who have high motivation will have high performance at PT Cahaya Bintang Manise, Salahutu District, Central Maluku Regency.